The Effects of Simulated Wildland Firefighting Tasks on Core Temperature and Cognitive Function under Very Hot Conditions - Williams-Bell, F. Michael; Aisbett, Brad; Murphy, Bernadette A.; Larsen, Brianna (Frontiers in Physiology, 2017)
Background: The severity of wildland fires is increasing due to continually hotter and drier summers. Firefighters are required to make life altering decisions on the fireground, which requires analytical thinking, problem solving, and situational awareness. This study aimed to determine the effects of very hot (45°C; HOT) conditions on cognitive function following periods of simulated wildfire suppression work when compared to a temperate environment (18°C; CON). Methods: Ten male volunteer firefighters intermittently performed a simulated fireground task for 3 h in both the CON and HOT environments, with cognitive function tests (paired associates learning and spatial span) assessed at baseline (cog 1) and during the final 20-min of each hour (cog 2, 3, and 4). Reaction time was also assessed at cog 1 and cog 4. Pre- and post- body mass were recorded, and core and skin temperature were measured continuously throughout the protocol. Results: There were no differences between the CON and HOT trials for any of the cognitive assessments, regardless of complexity. While core temperature reached 38.7°C in the HOT (compared to only 37.5°C in the CON; p < 0.01), core temperature declined during the cognitive assessments in both conditions (at a rate of -0.15 ± 0.20 °C.hr-1 and -0.63 ± 0.12 °C.hr-1 in the HOT and CON trial respectively). Firefighters also maintained their pre-exercise body mass in both conditions, indicating euhydration. Conclusions: It is likely that this maintenance of euhydration and the relative drop in core temperature experienced between physical work bouts was responsible for the preservation of firefighters’ cognitive function in the present study.